Digital quantification of miRNA directly in plasma using integrated comprehensive droplet digital detection1. Issue 21 (7th November 2015) - Zhang, Kaixiang; Kang, Dong-Ku; Ali, M. Monsur; Liu, Linan; Labanieh, Louai; Lu, Mengrou; Riazifar, Hamidreza; Nguyen, Thi N.; Zell, Jason A.; Digman, Michelle A.; Gratton, Enrico; Li, Jinghong; et al.
<x xml:space="preserve">Abstract</x> We present a technology that can provide digital quantification of miRNA in unprocessed plasma with a LOD of 50 copies per mL.